Lipid droplets and polyunsaturated fatty acid trafficking: Balancing life and death - Danielli, Mauro; Perne, Leja; Jarc Jovičić, Eva; Petan, Toni (Frontiers in Cell and Developmental Biology, 2023)
Lipid droplets (LD) are fat storage organelles ubiquitously distributed across the eukaryotic kingdom. They have a central role in regulating lipid metabolism and undergo a dynamic turnover of biogenesis and breakdown to meet cellular requirements for fatty acids (FAs), including polyunsaturated fatty acids (PUFAs). PUFAs esterified in membrane phospholipids define membrane fluidity and can be released by the activity of phospholipases A2 to act as ligands for nuclear receptors or to be metabolized into a wide spectrum of lipid signaling mediators. PUFAs in membrane phospholipids are also highly susceptible to lipid peroxidation, which if left uncontrolled leads to ferroptotic cell death. On the one hand, LDs act as antioxidant organelles that control PUFA storage in triglycerides (TAG) in order to reduce membrane lipid peroxidation, preserve organelle function and prevent cell death, including ferroptosis. On the other hand, LD breakdown fine-tunes the delivery of PUFAs into metabolic and signaling pathways, but unrestricted LD breakdown may also lead to the release of lethal levels of PUFAs. Precise regulation of LD turnover is thus essential for PUFA distribution and cellular homeostasis. In this review, we focus on emerging aspects of LD-mediated regulation of PUFA trafficking, including the management of membrane lipid peroxidation, ferroptosis and lipid mediator signaling.